The Antimicrobial Peptide Cecropin AD Supplement Alleviated Soybean Meal-Induced Intestinal Inflammation, Barrier Damage, and Microbial Dysbiosis in Juvenile Turbot, Scophthalmus maximus - Dai, Jihong; Ou, Weihao; Yu, Guijuan; Ai, Qinghui; Zhang, Wenbing; Mai, Kangsen; Zhang, Yanjiao (Frontiers in Marine Science, 2020)
This study aimed to investigate the benefit of dietary cecropin AD (CAD) on the intestinal health of turbot fed diets with a high level of soybean meal. A 12-week feeding trial was conducted with four isonitrogenous and isolipidic diets: a fishmeal-based diet (FM), a diet replacing 40% fish meal protein of FM diet with soybean meal protein (SBM), and the SBM diet supplemented with 500ppm (C1) and 1000ppm (C2) CAD, respectively. The results of intestine histology showed that turbots fed the SBM diet exhibited distinct symptoms of enteritis, however, fish fed diets with CAD supplementation kept the normal appearance of the distal intestine which was similar to that in FM group. Compared with the SBM group, diet with CAD supplementation significantly decreased the gene expression level of intestinal pro-inflammatory cytokines TNF-α, IL-1β, IFN-γ, and NF-κB, while up-regulated the gene expression level of intestinal tight junction proteins Claudin-3, Claudin-4, Occludin, and ZO-1. Besides, diet C1 shaped the intestinal microbiota profile towards an anti-inflammatory phenotype represented by the increased abundance of Blutia, Firmicutes/Bacteroides ratio, and decreased Prevotellaceae. In conclusion, dietary CAD could positively modulate the intestinal health of turbot from the impairment induced by soybean meal, which expands its application to help fish better adapt to the increasing plant protein in aquafeed.